POLA ASUH ORANG TUA DALAM UPAYA KURATIF TERHADAP PERILAKU AGRESIF ANAK DI RA AL-HIDAYAH PRAGAAN SUMENEP - Affandi, Qaniatul Aufa (JURNAL SETIA PANCASILA, 2021)
This research is about parenting in curative efforts towards aggressive children's behavior in the digital age which aims to determine the form of parenting that can reduce and successfully overcome the aggressive behavior of children in the digital era. The method of this research uses qualitative methods with qualitative descriptive types that attempt to describe the form of parenting that can reduce and successfully overcome the aggressive behavior of children in the digital era. The results of this study are six forms of efforts that are often used by parents at RA Al-Hidayah to reduce their children's aggressive behavior caused by gadget addiction, namely as follows: diverting to preferred activities, diverting to more productive activities, giving advice , provides education on the dangers of gadgets, provides a good role model, controls social interactions and children's playtime. The above efforts include democratic parenting because these efforts are in accordance with the characteristics of democratic parenting.